2009
DOI: 10.1177/1753425909339815
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a C1q/C1qR system regulates monocyte-derived dendritic cell differentiation at the interface of innate and acquired immunity

Abstract: Growing evidence shows that C1q modulates the growth and function of cells committed to the monocyte-derived dendritic cell (DC) lineage. Because C1q regulates both innate and acquired immune responses, we postulated that C1q modulates the transition from monocytes to DCs, i.e. the interface between innate and acquired immunity. Human peripheral blood monocytes cultured with soluble C1q and DC growth factors (GM-CSF + IL-4) failed to down-regulate monocyte-associated (CD14, CD16) and up-regulate DC-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
68
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 56 publications
2
68
1
Order By: Relevance
“…Although C1q deficiency in SLE has led to the concept that complement-independent functions of C1q include maintenance of immune tolerance, the mechanism(s) by which C1q deficiency contributes to SLE remains poorly defined, as does the means by which C1q sustains immune homeostasis in general. Because excessive immunological activation is thought to be driven by monocyte-derived DCs and pDCs in SLE, and because LAIR-1 and C1q have been independently reported to inhibit functions of both DC subtypes in a similar fashion (4,5,7,14,15), we propose that defects in C1q and LAIR-1 interactions contribute to immune pathology in this disease.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although C1q deficiency in SLE has led to the concept that complement-independent functions of C1q include maintenance of immune tolerance, the mechanism(s) by which C1q deficiency contributes to SLE remains poorly defined, as does the means by which C1q sustains immune homeostasis in general. Because excessive immunological activation is thought to be driven by monocyte-derived DCs and pDCs in SLE, and because LAIR-1 and C1q have been independently reported to inhibit functions of both DC subtypes in a similar fashion (4,5,7,14,15), we propose that defects in C1q and LAIR-1 interactions contribute to immune pathology in this disease.…”
Section: Discussionmentioning
confidence: 92%
“…C1q not only opsonizes apoptotic debris to prevent SLE (1, 6) but suppresses IFN-α production by plasmacytoid dendritic cells (pDCs) in SLE (4,5). Reports that C1q engages cellular C1q receptors to inhibit differentiation of monocytes to DCs (7,8) provide further evidence that C1q may directly interact with immune cells to induce tolerance and inhibit autoimmunity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that p32 interaction with its ligands may control the differentiation of inflammatory cells, such as macrophages and dendritic cells (27). Regardless of what its pathophysiological roles might be, it is clear that cell surface p32 expression and high LyP-1 binding are potentially useful markers for a class of inflammatory cells associated with atherosclerotic plaques and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although both gC1qR and cC1qR lack a consensus motif for a transmembrane segment, each has been shown to recruit signaling partners with transmembrane domains. For example, some putative signaling partners for cC1qR include CD91 on monocytes, 16 8,9,24,25 However, whereas both C1q receptors are present on the surface of immature DCs (iDCs), little is known about their possible signaling partners on these cells.iDCs, but not mature DCs, are a primary source of active C1q. 1,26 Human monocyte-derived iDCs express high levels of both gC1qR and cC1qR, and their surface levels decrease in a maturation-dependent manner.…”
mentioning
confidence: 99%